Women’s role in family economic resilience in the time of the Covid-19 pandemic according to Islamic perspective - Rizky Andrean; Hendri Hermawan Adinugraha; Achmad Tubagus Surur (Review of Islamic Social Finance and Entrepreneurship, 2022)
Purpose – This paper tries to examine and explain how the role of women in the economic resilience of the family during the Covid-19 pandemic from an Islamic perspective. Methodology – The method in this research is a phenomenological study and also a descriptive analysis. This research is a literature study or library research using a qualitative research approach. This study uses secondary data originating from the publication of scientific journal articles, the results of previous studies, and other reference sources that are relevant to the thing being studied. Findings – The results of the study show that working women play a very important role in maintaining the economic resilience of the family, especially during the pandemic. However, on the other hand, women who help make a living also have their challenges, namely how they can divide their time between working to earn a living and also taking care of the household. Implications – Working women must be able to balance the roles they have. Islam allows women who work to help earn a living with the record that it is with the permission of her husband, to avoid things that are contrary to the Shari’a, and also stay away from work that is contrary to her feminine nature.Originality – Religious teachings that serve as guidelines in life will also be a separate perspective that will enrich views on how women work.